Онтологічний підхід до оперативного планування - Тихонов, Юрій Леонтійович; Лахно, Валерій Анатолійович (НТУ "ХПІ", 2018)
У даній роботі пропонується онтологізований опис об'єктів, що потребують планування заходів. Це дозволяє згрупувати і об'єднати всі необхідні дані в одному документі для вирішення різних завдань, зокрема для планування оперативних дій. Підхід відрізняється застосуванням КО, що забезпечують систематизацію концептів, врахування їх взаємозв'язку та дає можливість створення інструментарію планування дій. Подібний підхід можна використовувати в різних галузях. В роботи наведені приклади застосування для планування заходів щодо захисту даних та планування випуску електронних курсів.

Planning is a relatively independent subsystem, which covers a set of special tools, rules, structural bodies, information flows and processes aimed at the preparation and implementation of plans. The purpose of the planning process is to try to take into account, whenever possible, all internal and external factors that provide favorable conditions for the normal functioning of the objects. There is a number of planning techniques that determine the content, form, structure and procedure for developing a plan. However, there is no toolkit based on systematized and structured description of objects and events. One of the successful approaches to describing such models is an ontological one, where in the formalized form the knowledge of the subject field is presented. The ontological aspects of the description include a range of issues ranging from structuring information and characteristics to the linkages of objects and activities. Among the features of the ontological description, we note the presence of levels of concepts and explicit indication of categories of higher order. In this paper, an ontology description of objects requiring action planning is proposed. This allows you to group and combine all the necessary data in one document to solve various tasks, in particular for planning operational actions. The approach is different in applying KO, which ensures the systematization of concepts, taking into account their interconnections, and gives the opportunity for creating tools for action planning. A similar approach can be used in various fields. The examples of application for planning data protection measures and planning of the issuance of electronic courses are given in the work.
Ontological approach to operational planning
Keywords: онтологизований опис; прогнозування; ондограф; екологічний паспорт; база знань; ontology description; forecasting; ontograph